2021
DOI: 10.3390/cancers13112847
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Classification to Prognosticate Response in Medically Managed Endometrial Cancers and Endometrial Intraepithelial Neoplasia

Abstract: Background: The aim of this study was to evaluate whether molecular classification prognosticates treatment response in women with endometrial cancers and endometrial intraepithelial neoplasia (EIN) treated with levonorgestrel intrauterine system (LNG-IUS). Methods: Patients treated with LNG-IUS for endometrial cancer or EIN from 2013 to 2018 were evaluated. Using immunohistochemistry and single gene sequencing of POLE, patients were classified into four groups as per the Proactive Molecular Risk Classifier fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…After literature searching, we found three studies that tested the PromisE classifier on EC patients who received FPT so far ( 11 13 ). The characteristics and outcome measures of each study are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After literature searching, we found three studies that tested the PromisE classifier on EC patients who received FPT so far ( 11 13 ). The characteristics and outcome measures of each study are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Puechl et al. ( 13 ) reported that 1/4 of EC patients with MMR-D and 4/17 with p53wt developed progression or underwent definitive surgery after levonorgestrel intrauterine system (LNG-IUS) treatment. They also included 37 endometrial intraepithelial neoplasia (EIN) patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study performing molecular analysis on 15 fully evaluable EC patients, three of the eight patients in the CN-L subgroup respectively relapsed at the 8th, 11th, and 41st months of conservative treatment ( 22 ). Another study showed similar results ( 24 ), suggesting the lack of the effective molecular signature of the CN-L subgroup might impair the value of the molecular strategy to stratify the patients under fertility-preservation treatment. All these problems suggest that further molecular stratification to subdivide the patients is urgently needed.…”
Section: The Molecular Classification Of Ecmentioning
confidence: 83%
“…The patients under fertility-preservation treatment might also profit from the molecular classification. Since the conventional progesterone receptor and estrogen receptor isoforms showed insufficient predictive accuracy ( 21 ), the ProMisE strategy has also been practiced in the population of fertility preservation to identify the MSI status and the potential TP53 abnormality ( 22 24 ). POLE mutation could be detected only by sequencing (the next-generation sequencing or Sanger sequencing), considering its superior prognostic value, and it might be of use for young patients with strict fertility-spared conditions.…”
Section: The Molecular Classification Of Ecmentioning
confidence: 99%